Pengaruh Kompensasi, Lingkungan Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan: Studi Kasus PT. Gizindo Pratama - Yunan Mahardhika; Kasmari Kasmari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
PT. Gizindo Pratama Semarang is a company engaged in the trade and production of cow's milk, goat's milk, and soy milk. The purpose of this study was to determine the effect of compensation, work environment, and work motivation on employee performance at PT. Gizindo Pratama Semarang. The sampling technique in this study used nonprobability sampling, which is a sampling technique that does not provide equal opportunities or chances for each element or member of the population to be selected as a sample. The analysis method used is multiple linear regression analysis using SPSS version 25 software. The results of the study indicate that compensation, work environment, and work motivation have a positive effect on employee performance.